Encapsulação de óleos de alto valor nutricional para formulação de alimentos - Rojas, Valquiria Maeda (2018)
There is an increasing demand for healthy foodstuff or foods with specific properties such as the polyunsaturated fatty acids (PUFAs). Microencapsulation is a technology that is able to protect PUFA-rich oils from oxidation during processing and storage. The objective of this work was to microencapsulate chia seeds, green coffee, pumpkin seeds, walnut and baru oils and to formulate mayonnaise and whey protein. Microparticles characterization demonstrated that oils were efficiently encapsulated (85% efficiency) and microparticles presented diameter inferior of 100 micrometers. Thermal analyses indicated an increase in the thermal stability of the oils after encapsulation. Mayonnaise was formulated with microparticles containing chia seeds, pumpkin seeds or baru oils while the microparticles containing walnut or green coffee oils were used to formulate whey protein. Rheology analyses showed that the presence of the microcapsules influenced the mayonnaise properties, however were not able to distinguish samples containing up to 5%wt microcapsules from the blank mayonnaise sample in the sensorial test. Whey protein containing microencapsulated green coffee oil presented green color which could explain the low preference from the consumers when compared to the blank sample, however, rheology analyses did not indicate changes in properties of this product. Overall, the encapsulation strategy applied was efficient to protect the oil from oxidation and enriched foodstuff were successfully produced with the microcapsules.